Binding of 131I-Labeled Tissue-Type Plasminogen Activator on De-Endothelialized Lesions in Rabbits - Uehara, A.; Isaka, Y.; Etani, H.; Kimura, K.; Yoneda, S.; Kamada, T.; Kozuka, T.; Nobuhara, M. (Nuklearmedizin - NuclearMedicine, 1987)
Tissue-type plasminogen activator (t-PA) which has a high affinity for fibrin in the clot, was labeled with 131I by the iodogen method, and its binding to de-endothelialized lesions in the rabbit was measured to assess the detectability of thrombi. The de-endothelialized lesion was induced in the abdominal aorta with a Fogarty 4F balloon catheter. Two hours after the de-endothelialization, 131I-labeled t-PA (125 ± 46 μCi) was injected intravenously. The initial half-life of the agent in blood (n = 12) was 2.9 ± 0.4 min. The degree of binding of 131I-labeled t-PA to the de-endothelialized lesion was evaluated at 15 min (n = 6) or at 30 min (n = 6) after injection of the agent. In spite of the retention of the biochemical properties of 131I-labeled t-PA and the presence of fibrin deposition at the de-endothelialized lesion, the binding of t-PA to the lesion was not sufficiently strong. Lesion-to-control ratios (cpm/g/cpm/g) were 1.65 ± 0.40 (at 15 min) and 1.39 ± 1.31 (at 30 min), and lesion-to-blood ratios were 1.39 ± 0.32 (at 15 min) and 1.36 ± 0.23 (at 30 min). These results suggest that radiolabeled t-PA may be inappropriate as a radiopharmaceutical for the scintigraphic detection of a pre-existing thrombotic lesion.Gewebespezifischer Plasminogen-Aktivator (t-PA), der im Gerinnsel eine hohe Affinität zu Fibrin hat, wurde mit Hilfe der Jodogen-Methode mit 131J markiert. Bei der Ratte wurde seine Anreicherung in einer Endothelläsion gemessen, um herauszufinden, inwieweit Thromben damit nachweisbar sind. Die Desendothelialisierung dér Bauchaorta in dér Ratte wurde durch einen Fogarty-4F-Ballon-Ka-theter vorgenommen. Zwei Stunden nach der Desendothelialisation wurde 131J-markiertes t-PA (125 ± 46 (μCi, Mittel ± Standardabweichung) intravenös injiziert. Die initiale Halbwertszeit der Substanz im Blut (n = 12) lag bei 2,9 ± 0,4 min.Das Ausmaß der Anreicherung des 131J-markierten t-PA in der Endothelverletzung wurde 15 min (n = 6) oder 30 min (n = 6) nach Gabe dieser Substanz ermittelt. Obwohl die biochemischen Eigenschaften des 131J-markierten t-PA unverändert blieben und die Fibrinablagerung in der Endothelläsion vorhanden war, war die Bindung des 131J-markierten t-PA an der Läsion nicht ausreichend, wie im folgenden gezeigt wird. Die Verhältnisse Läsion zu Kontrolle (cpm/g/cpm/ g) waren 1,65 ± 0.40 (nach 15 min) und 1,39 ± 1,31 (nach 30 min), und die Verhältnisse Läsion zu Blut ± 0,32 (nach 15 min) und 1,36 ± 0,23 (nach 30 min). Aufgrund dieser Ergebnisse scheint radioaktiv markiertes t-PA als Radiopharmazeutikum für den szintigraphischen Nachweis einer vorbestehenden thrombotischen Läsion nicht geeignet zu sein.